ANALYSIS OF THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP BEHAVIOR AND EMPLOYEE CREATIVITY AT THE OFFICE OF COOPERATIVES AND SMES, SOUTHEAST SULAWESI PROVINCE - Ade Marsalena, Nindy; Azis Muthalib, Dzulfikri (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to determine and analyze the relationship between transformational leadership behavior and employee creativity at the Department of Cooperatives and SMEs in Southeast Sulawesi Province. The population in this study were employees at the Department of Cooperatives and SMEs of Southeast Sulawesi Province. The research sample was 61 employees at the Department of Cooperatives and SMEs of Southeast Sulawesi Province. This study uses simple linear regression analysis. The results showed that transformational leadership behavior had a positive and significant relationship with the creativity of employees at the Department of Cooperatives and SMEs in Southeast Sulawesi Province. Changes in increasing transformational leadership behavior are positive and real towards increasing employee creativity at the Department of Cooperatives and SMEs in Southeast Sulawesi Province. This fact shows that good transformational leadership behavior has a contribution in increasing the creativity of employees at the Cooperatives and UMKM Office of Southeast Sulawesi Province.